‘Great powers and great responsibilities’: a brief comment on A brief mobile app reduces nonsuicidal and suicidal self-injury: evidence from three randomized controlled trials (Franklin et al., 2016) - Nielsen, Emma; Kirtley, Olivia; Townsend, Ellen (American Psychological Association, 2016)
Online and mobile mental health applications (apps) herald exciting new opportunities for the treatment and prevention of self-injurious thoughts and behaviors (SITBs). With such rapid technological advances it is paramount that healthcare innovation is not achieved to the detriment of intervention quality. Franklin et al’s., (2016) Therapeutic Evaluative Conditioning (TEC) app is a novel and timely addition to the mobile health landscape; uncommonly for such apps, it is evidence-based. There are, however, several crucial challenges to be surmounted for TEC to be successful; arguably, interventions ought to build lasting skills that can be subsequently and consciously recruited to manage distress beyond the intervention period. Furthermore, SITBs are a coping mechanism, albeit maladaptive, thus extinguishing SITBs via TEC must be bolstered by the development of alternative coping strategies, particularly if the psychological distress that underlies SITBs is not addressed therapeutically. Stigma exacerbates the psychological distress of those engaging in SITBs, thus we question whether the types of stimuli employed in TEC may further add to this stigma, potentially impacting upon future help-seeking. One solution may be to explore a positive only TEC; enhancing positive self-worth may provide a more sustainable and meaningful treatment target, particularly when used as an adjunct to therapy or as a waitinglist intervention. Mobile interventions for SITBs bring unique ethical challenges, including individuals’ right to be fully informed about potentially distressing stimuli. The current commentary aims to highlight the methodological and ethical challenges faced by TEC and encourage further discussion around this topic.